Presos em nome da ordem: As prisões preventivas e a suposta solução à subversão pernambucana em 1964. - Correia, Raphael Henrique Roma (2017)
This work deals with Preventive Prisons carried out by the security and information organs immediately after the civil-military coup in Pernambuco in the year 1964, it is mainly tried to problematize the reasons and justification of these detentions. It also seeks to explore the social context of the 1950s and 1960s in Pernambuco; analyze the structuring and operation of the institutions responsible for security in that period; and give evidence to the trajectories of anonymous lives that had the everyday invaded by the idea of standardization instituted to justify the implementation of the state of exception. The sources used in the dissertation were, mainly, the documents of the DOPS / PE, in particular the Functional Report 26.981, and the oral reports of memory of the CEHIBRA of the Joaquim Nabuco Foundation and of the Project Marcas da Memória. In pursuit of these objectives, the study draws on several historiographic methods and theories such as, without a hierarchical sense, New Political History, Oral History, Biopolitics, among others.